IBM SPSS modeler essentials : effective techniques for building powerful data mining and predictive analytics solutions - Salcedo, Jesus; McCormick, Keith (Consultant) (Packt Publishing, 2017)
IBM SPSS Modeler allows quick, efficient predictive analytics and insight building from your data, and is a popularly used data mining tool. This book will guide you through the data mining process, and presents relevant statistical methods which are used to build predictive models and conduct other analytic tasks using IBM SPSS Modeler. From ...